Pelatihan Public Speaking Radio Bagi Pelajar SMAN 10 Kota Semarang Menggunakan Aplikasi Zararadio - Pamugkas, Yoma Bagus; Azalea, Nabila; Mambat, Benita Nydia; Ananda, Nia; Maysun, Jessenia (Fakultas Teknologi Informasi dan Industri Unisbank, 2024)
In everyday life humans can never be separated from communication. Public speaking skills or public speaking are still not fully owned by students. Radio is a popular mass media as a source of information needed by the public. One of the important benchmarks for a radio station is the existence of an announcer. So it is necessary to have knowledge of speaking techniques as a radio announcer. To measure the level of understanding of the participants, the manager conducted a pre-test and post-test followed by observations during the practice of radio public speaking. The results of this service activity really helped the trainees in increasing their knowledge, understanding as well as skills in public speaking and broadcasting.